Cluster based Routing Protocol for Mobile Ad Hoc Networks - Rezaee, M.; Yaghmaee, M. (INFOCOMP Journal of Computer Science, 2009)
In this paper, we proposed a cluster based routing protocol for mobile ad hoc network. It uses clustering's structure to decrease average end-to-end delay and improve the average packet delivery ratio. We simulate our routing protocol for nodes running the IEEE802.11 MAC. Results of our experiments show that the packet delivery ratio increases greatly and packet delay decreases significantly. In proposed method the routing is also done quickly and its error tolerance increases. The reason is that, routing is depended on the address of cluster heads. By failing any node in the route, its cluster head may use another node to forward packets (if available). This causes the error tolerance to enhance.